1950
DOI: 10.1103/physrev.79.405
|View full text |Cite
|
Sign up to set email alerts
|

Superconducting Bismuth Alloys

Abstract: 40 PULSE HEIGHTFIG. 2, Coincidence counting rate in a small pulse-height interval as a function of pulse height. Pulse-height interval was 2.5 pulse-height divisions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
16
0

Year Published

1955
1955
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 2 publications
3
16
0
Order By: Relevance
“…Its topological feature has been analyzed according to the band inversion occurrence between Na- s and Bi- p orbits at the Γ point, the Z 2 number based on the derived parities, and the two selected surface non-trivial helical states. Without (with) the spin-orbit coupling (SOC) effect the super-conducting transition temperature of T c is derived to be 1.82–2.59 (2.92–3.75) Kelvin from the electron-phonon coupling strength λ = 0.71 (0.84) and the average velocity < ω > ln = 40.8 (38.7) cm −1 , agreeing well with the experimental findings 44 45 . In addition, by considering phonon vibrational eigenvalues in the whole of Brillioun zone (BZ) and the phonon relaxation time derived from third-order force constants, we have further revealed that NaBi exhibits an extremely low lattice thermal conductivity but an obviously anisotropic feature of along the a -axis and along the c -axis at room temperature, respectively.…”
supporting
confidence: 80%
“…Its topological feature has been analyzed according to the band inversion occurrence between Na- s and Bi- p orbits at the Γ point, the Z 2 number based on the derived parities, and the two selected surface non-trivial helical states. Without (with) the spin-orbit coupling (SOC) effect the super-conducting transition temperature of T c is derived to be 1.82–2.59 (2.92–3.75) Kelvin from the electron-phonon coupling strength λ = 0.71 (0.84) and the average velocity < ω > ln = 40.8 (38.7) cm −1 , agreeing well with the experimental findings 44 45 . In addition, by considering phonon vibrational eigenvalues in the whole of Brillioun zone (BZ) and the phonon relaxation time derived from third-order force constants, we have further revealed that NaBi exhibits an extremely low lattice thermal conductivity but an obviously anisotropic feature of along the a -axis and along the c -axis at room temperature, respectively.…”
supporting
confidence: 80%
“…Since 1950 several authors [ 5 8 ], have experimentally studied disordered samples of bismuth and have determined the corresponding PDFs. In general, most authors agree that the structure of a-Bi is very similar to the corresponding liquid, but it was not until 1969 when Fujime [ 2 ] characterized and gave the following arguments to say that his bismuth sample was amorphous: the PDF obtained by Fujime had 3 peaks, the first one located at 3.28 Å, the second one at 4.5 Å and the third at 6.5 Å; it has a coordination number of N = 5.6, where N was obtained by integrating a Gaussian-like curve adjusted to the first peak of J ( r ) = 4 πr 2 g ( r ).…”
Section: Introductionmentioning
confidence: 99%
“…For the binary bismuth compounds, some of them show superconductivity, such as KBi 2 (3.6 K), 11 SrBi 3 (5.62 K), 12 BaBi 3 (5.69 K), 12 Rh 3 Bi 14 (2.94 K), 13 and In 2 Bi (5.9 K). 14 For KBi 2 , except superconducting transition temperature T c , the studies on its physical properties are scarce and its classification of superconductivity has not been identified yet.…”
Section: Introductionmentioning
confidence: 99%
“…14 For KBi 2 , except superconducting transition temperature T c , the studies on its physical properties are scarce and its classification of superconductivity has not been identified yet. 11,15 In this work, we performed the detailed characterization and analysis of physical properties for KBi 2 single crystals in superconducting and normal states. Experimental and theoretical calculation results undoubtedly indicate that KBi 2 is a type-I SC in the dirty limit.…”
Section: Introductionmentioning
confidence: 99%